Methodology to Update Flood Risk Areas in the Municipality of Florencia (Caquetá) Through Overflights of Remotely Piloted Aircraft - Millán Rojas, Edwin Eduardo; Arenas Romero, Roland Ricardo; Vidales Claros, Sebastián (Ingeniería Solidaria, 2018)
Introduction: This article derives from the research conducted as a graduation option in the internship at the Agustín Codazzi Geographical Institute, Caquetá office, Colombia, during the second half of 2017, supported by the Systems Engineering program at the Universidad de la Amazonia. Aim: To design a methodology to update cadastral information of risk areas using a remotely piloted aircraft in the Colombian Amazonian piedmont to determine the impact caused by the phenomenon of floods. Materials and methods: Two research methods were used: the first one was exploratory, based on which the sources and theoretical references for the methodology design were established. The second one was forward-looking, with which a methodological design was proposed to address the problem of updating risk areas. The study area included a wooded sector on the edge of La Perdiz brook in the municipality of Florencia. Conclusions: The methodology designed allowed to determine the existence of 98 properties in risk areas by means of delimitation in the study area, establishing the correct functionality of the proposed invention. Originality: The development of a methodology for cadastral updating allows to integrate hardware technology easily and obtain detailed information to prevent natural disasters such as floods. Limitations: The project only covers the urban areas of the Colombian Amazonian piedmont, given the little information available from the rural land register in these areas of the country.